Liturgie en Letterkunde: ’n ‘Herfs’-liturgie vir Paasfees in die Suidelike Halfrond - Vos, Casparus Johannes Adam (Verbum et ecclesia, 2013)
Liturgy and Literature - An Autumn liturgy for Easter in the Southern Hemisphere. The aim of this article was to explore possibilities regarding the liturgical inculturation of the Easter liturgy in the Southern Hemisphere. The Easter liturgy originated in the Northern Hemisphere, where it was and is celebrated during Spring with all its concomitant symbolism of new life. That symbolism seems to be lacking in the Easter liturgy in the Southern Hemisphere, where Easter occurs during Autumn. In order to address this issue an interdisciplinary exploration of the themes of both the Easter liturgy and the liturgical ordo was undertaken, as well as a study of Afrikaans poems about Autumn. An example of a liturgy making use of the ecumenical-protestant fourfold order of worship [ordinarium] and enriched with liturgical elements based on the poems studied here as well as some traditions relating to the Easter liturgy [proprium] is presented. As a whole this article serves as an example of how Liturgical Studies can seek alliances with other disciplines in order to address its own questions and for its own purposes.